Les universitaires béninoises face aux hiérarchies dans la production des savoirs francophones sur le genre - Lucia Direnberger; Yvette Onibon Doubogan (Genre, Sexualité et Société)
This article addresses the material conditions of scientific knowledge produced by scholars working on gender in Benin. It shows how gender inequalities within academia, the importance of development agencies in Benin, but also the international division of scientific work and systemic racism in European and north American academia structure the careers of these academics, and make difficult the institutionalization of gender studies in Benin. This article is based on semi-structured interviews conducted with about twenty academics, from various disciplines of human and social sciences and of different statuses, working on women and / or gender in human and social sciences in Benin universities. It shows that the institutionalization of gender studies, the precariousness of academics specializing in this field and gender inequalities in Benin universities feed on the interdependence between the international division of scientific work and gender and race inequalities in the academic centers of the North.